STUDI FASIES AIR TANAH DI KAMPUS LAPANGAN PPSDM GEOMINERBA DAERAH CIPATAT, KABUPATEN BANDUNG BARAT, PROVINSI JAWA BARAT - Setiawan, Iwan Fahlevi; Rohaendi, Nendi; Wahyudi, Wahyudi (PPSDM Geominerba, 2023)
PPSDM Geominerba Field Campus is a center for training practice activities located in Cipatat, Padalarang District, Kab. Bandung Barat. The existence of groundwater plays an important role in supporting training practices and daily needs for the surrounding community. The aim of this paper is to determine the facies of groundwater based on data on physical and chemical properties. Samples were taken from 5 spring locations to be analyzed in the laboratory and re-analyzed using the trilinear piper diagram. The acidity level of spring water is < 7, with values ​​varying between 4.99 – 6.31, Total Dissolved Solid (TDS) is in the range of 0.12 – 0.37 mg/l, Electrical Conductivity value (EC) between 0.26 – 0.74 µS. Based on the plotting results from the piper diagram, it was found that the research area could be grouped into 2 groundwater facies: Facies Ca, HCO3- and Facies No Dominant, HCO3-